Frequency and predictors of estimated HIV transmissions and bacterial STI acquisition among HIV-positive patients in HIV care across three continents - Steven A. Safren (2018)
© 2016 Safren SA et al. Introduction: Successful global treatment as prevention (TasP) requires identifying HIV-positive individuals at high risk for transmitting HIV, and having impact via potential infections averted. This study estimated the frequency and predictors of numbers of HIV transmissions and bacterial sexually transmitted infection (STI) acquisition among sexually active HIV-positive individuals in care from three representative global settings. Methods: HIV-positive individuals (n = 749), including heterosexual men, heterosexual women and men who have sex with men (MSM) in HIV care, were recruited from Chiang Mai (Thailand), Rio De Janeiro (Brazil) and Lusaka (Zambia). Participants were assessed on HIV and STI sexual transmission risk variables, psychosocial characteristics and bacterial STIs at enrolment and quarterly for 12 months (covering 15 months). Estimated numbers of HIV transmissions per person were calculated using reported numbers of partners and sex acts together with estimates of HIV transmissibility, accounting for ART treatment and condom use. Results: An estimated 3.81 (standard error, (SE) = 0.63) HIV transmissions occurred for every 100 participants over the 15 months, which decreased over time. The highest rate was 19.50 (SE = 1.68) for every 100 MSM in Brazil. In a multivariable model, country×risk group interactions emerged: in Brazil, MSM had 2.85 (95% CI = 1.45, 4.25, p<0.0001) more estimated transmissions than heterosexual men and 3.37 (95% CI = 2.01, 4.74, p<0.0001) more than heterosexual women over the 15 months. For MSM and heterosexual women, the combined 12-month STI incidence rate for the sample was 22.4% (95% CI = 18.1%, 27.3%; incidence deemed negligible in heterosexual men). In the multivariable model, MSM had 12.3 times greater odds (95% CI = 4.44, 33.98) of acquiring an STI than women, but this was not significant in Brazil. Higher alcohol use on the Alcohol Use Disorders Identification Test (OR = 1.04, 95% CI = 1.01, 1.08) was also significantly associated with increased STI incidence. In bivariate models for both HIV transmissions and STI incidence, higher depressive symptoms were significant predictors. Conclusions: These data help to estimate the potential number of HIV infections transmitted and bacterial STIs acquired over time in patients established in care, a group typically considered at lower transmission risk, and found substantial numbers of estimated HIV transmissions. These findings provide an approach for evaluating the impact (in phase 2 studies) and potentially cost-effectiveness of global TasP efforts.